An Eleven Years Analysis of the Seasonal Dynamics of Urban Heat Island (UHI) Intensity (2004-2014) - Sarah, Jatau; Louis, Mmaduka; Esae, Obidike Emeka (International Journal of Geography and Geology, 2020)
Urban heat island (UHI) intensity is the characteristic warmth of both the atmosphere and lithosphere in urban areas compared to its rural surrounding areas. This study observed the seasonal dynamics of UHI in Coventry city. ArcGIS was used to collect the land surface temperature (LST) of different seasons; summer, autumn, spring and fall using the peak month to represent each season. These data was collected during the night times to avoid cloud cover and limit other impeding factors for accurate data collection and results. The data was collected for a period of 11years that is 2004-2014. The study revealed that there was no regular pattern of UHI across the four seasons, however, it was discovered that there was a marginal increase in temperature in some regions during the seasons. To mitigate UHI effects this study recommends the planting of trees to moderate the microclimate as well as the use of green roofs to absorb more of CO² thereby modifying and regulating the climate.